2018
DOI: 10.26911/jepublichealth.2018.03.02.04
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Disability in Patients with Leprosy at Kelet Hospital, Central Java

Abstract: Background: Leprosy is a chronic disease caused by Mycobacterium leprae. World Health Organization (WHO) reported that the number of leprosy cases in 2015 was 211,973 in 108 countries in the world. The number of leprosy cases in Indonesia ranks third after India and Brazil. There are 14,000 (8%) leprosy cases with disability. This study aimed to determine factors affecting disability and Years of Life with Disability (YLD) attributable to leprosy in patients with leprosy at Kelet Hospital, Central Java. Subjec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 13 publications
0
2
0
3
Order By: Relevance
“…In them, educational status and years lost to disability (YLD) were inversely related. 9 Likewise Kaur et al in their study done at Varanasi found out that low level of awareness led to delayed time of diagnosis and increased chances of deformity and disability. 10 Therefore Illiteracy and low priority to self care remain a major deterrent to self reporting causing delayed treatment and subsequent disability.…”
Section: Discussionmentioning
confidence: 96%
“…In them, educational status and years lost to disability (YLD) were inversely related. 9 Likewise Kaur et al in their study done at Varanasi found out that low level of awareness led to delayed time of diagnosis and increased chances of deformity and disability. 10 Therefore Illiteracy and low priority to self care remain a major deterrent to self reporting causing delayed treatment and subsequent disability.…”
Section: Discussionmentioning
confidence: 96%
“…Hasil penelitian ini sejalan dengan penelitian yang dilakukan oleh Nadhiro, dkk (2018) hasil analisis menunjukkan bahwa perawatan diri memiliki pengaruh terhadap distabilitas penyakit kusta secara langsung (Nadhiroh, Dharmawan, & Murti, 2018).…”
Section: Self Care Penderita Kustaunclassified
“…Tingkat pendidikan mempunyai hubungan dengan kecacatan penderita kusta. Proporsi yang tinggi pada penderita kusta dengan pendidikan rendah mengakibatkan gaya hidup sehat juga rendah [13]. Rendahnya pendidikan sebagai salah satu faktor risiko terjadinya kecacatan pada penderita kusta, walau efek tersebut masih belum dimengerti secara jelas.…”
Section: Pembahasanunclassified
“…Ada hubungan antara perawatan diri dengan kecacatan fisik pada penderita kusta [16]. Perawatan diri memiliki pengaruh terhadap disabilitas penyakit kusta secara langsung [13]. Perawatan diri kusta sangat diperlukan untuk mencegah kecacatan baru dan kerusakan fisik penderita serta dapat mengurangi keparahan kecacatan fisik yang sudah ada sehingga produktivitas penderita kusta tetap terjaga [2].…”
Section: Pembahasanunclassified